Crab barrel syndrome: Looking through the lens of type A and type B personality theory and social comparison process - Uzum, Burcu; Ozdemir, Yasemin; Kose, Semra; Ozkan, Osman Seray; Seneldir, Okan (Frontiers in Psychology, 2022)
Introduction There are epistemological studies about the main concept, Crab Syndrome. In this context, the study aims to reveal the antecedents of the Crab Syndrome by evaluating the theoretical background of the Crab Barrel Syndrome within the framework of Social Comparison Theory. The main purpose of this study is to identify the precursors of crab barrel syndrome. In line with this main purpose, the study also aims to reveal the relationship between crab barrel syndrome behaviors and type A versus type B personalities, along with the effect of social comparison behaviors. Type A personality represents the personalities of individuals who are stressed, ambitious, competitive, and quickly take action for their aims. Type B, on the other hand, presents the personality types of individuals who are calm, away from competition, and perform their actions slowly. Method It is designed quantitatively, employing scales to quantify type A and type B personalities, social comparison, and crab barrel syndrome. Hypotheses are tested using structural equation modeling. Result/discussion It is found that there is a positive relation between the type A personality and the crab barrel syndrome, and a negative one between the syndrome and high self-esteem. The findings suggest that by social comparison, type A and type B personality are precursors of crab barrel syndrome. In the study, the theoretical background of the Crab Syndrome was evaluated within the scope of Social Comparison Theory. In this context, examining the relationship between different organizational behavior theories and crab syndrome is important for other studies.